2017
DOI: 10.3233/jvr-170862
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity Partners Project: Multi-systemic knowledge translation and business engagement strategies to improve employment of people with disabilities

Abstract: Abstract. BACKGROUND:Fragmented employment service systems, a lack of information about disability across sectors, and a wide disconnect between the efforts to employ people with disabilities and the needs of the business community, have presented barriers to the adoption of best practices and effective implementation of new policies designed to improve the employment rate of people with disabilities. OBJECTIVE: The goal of the Diversity Partners Project is to develop, test, and launch an innovative learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In a 2016 review of the literature regarding demand-side factors and their impact on improving competitive employment rates for people with intellectual and developmental disabilities, only six studies were found which specifically sought to capture employer perspectives as the study population (Ellenkamp, et al, 2016). Those find-ings are consistent with the literature scan conducted during the 2015 development phase of the Diversity Partners Project, which uncovered nine articles directly relating to effective business engagement practices, most of which were descriptive in nature (Harris, et al, 2017). The challenge remains not only to identify promising and evidence-based employer engagement practices, but to develop effective methods of encouraging the adoption and use of those practices in community-based organization settings (Gilbride & Sensrud, 2008).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a 2016 review of the literature regarding demand-side factors and their impact on improving competitive employment rates for people with intellectual and developmental disabilities, only six studies were found which specifically sought to capture employer perspectives as the study population (Ellenkamp, et al, 2016). Those find-ings are consistent with the literature scan conducted during the 2015 development phase of the Diversity Partners Project, which uncovered nine articles directly relating to effective business engagement practices, most of which were descriptive in nature (Harris, et al, 2017). The challenge remains not only to identify promising and evidence-based employer engagement practices, but to develop effective methods of encouraging the adoption and use of those practices in community-based organization settings (Gilbride & Sensrud, 2008).…”
Section: Introductionmentioning
confidence: 67%
“…A secondary aim of the project is to increase representation of people with disabilities in career-driven training and supports within the public workforce development system, as well as secondary and post-secondary education and training programs. Diversity Partners utilized a knowledge translation (KT) framework to design a multi-faceted intervention, as described in Harris, Switzer, and Gower (2017). The National Institute on Disability Independent Living and Rehabilitation Research defines KT as the "multidimensional, active process of ensuring that new knowledge gained through the course of research ultimately improves the lives of people with disabilities, and furthers their participation in society" (NIDRR, 2005).…”
Section: A Knowledge Translation Projectmentioning
confidence: 99%